2015
DOI: 10.1016/j.jmmm.2015.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic relaxation and correlating effective magnetic moment with particle size distribution in maghemite nanoparticles

Abstract: The role of particle size distribution inherently present in magnetic nanoparticles (NPs) is examined in considerable detail in relation to the measured magnetic properties of oleic acid-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 38 publications
(84 reference statements)
4
39
0
Order By: Relevance
“…We have also plotted the T bif in Fig. 5(d) as a function of growth pressure; here T bif is the temperature at which the FC curve bifurcates from the ZFC curve 44 . Figure 6(a) shows the FC curves measured in applied H = 1 kOe; it is evident that all the thin films synthesized at different growth pressures exhibit ferromagnetic behavior (as also confirmed in the next figure) since as in ferromagnets, M gradually decreases with increase of temperature up to the Curie temperature (300-345 K here) ( Fig.…”
Section: Magnetic Properties Of Lsmo Thin Filmsmentioning
confidence: 99%
“…We have also plotted the T bif in Fig. 5(d) as a function of growth pressure; here T bif is the temperature at which the FC curve bifurcates from the ZFC curve 44 . Figure 6(a) shows the FC curves measured in applied H = 1 kOe; it is evident that all the thin films synthesized at different growth pressures exhibit ferromagnetic behavior (as also confirmed in the next figure) since as in ferromagnets, M gradually decreases with increase of temperature up to the Curie temperature (300-345 K here) ( Fig.…”
Section: Magnetic Properties Of Lsmo Thin Filmsmentioning
confidence: 99%
“…The particle dimensions were evaluated by HR-SEM measurements, where a drop of the nanoparticle solution was spread onto a Carbon Film 300 Mesh Cu. The size distribution for all NPs was fitted to the log-normal distribution with Do = median particle diameter and D = width of the distribution with average particle diameter <D>, and standard deviation [33]. Spherical Ag NPs with an average particle diameter <D> of 12.7 ± 1.2 nm (Figure 3) were found.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, previous experimental studies have shown that the distribution of F particle sizes plays a key role for the understanding of ferromagnetic nanoparticle behavior. 26,[52][53][54] In the following, a lognormal distribution of particle diameters is used with a mean diameter < d >= 8.29 nm and standard deviation σ sd = 2.99 nm. It should be noted that previous studies have shown that lognormal distributions are often observed in experimental systems.…”
Section: B Size-distributed Fm Particlesmentioning
confidence: 99%
“…It should be noted that previous studies have shown that lognormal distributions are often observed in experimental systems. 22,29,52,54,55 The nanoparticles are assumed to be all aligned along their easy axis. Figure 8 (left axis, round red symbols) shows the normalized particle size distribution D in the range of (4 to 25) nm, for 100 discrete d values.…”
Section: B Size-distributed Fm Particlesmentioning
confidence: 99%